1996
DOI: 10.1093/oxfordjournals.humrep.a019120
|View full text |Cite
|
Sign up to set email alerts
|

Endocrinology: Nuclear maturity and oocyte morphology after stimulation with highly purified follicle stimulating hormone compared to human menopausal gonadotrophin

Abstract: Several studies have shown that high concentrations of luteinizing hormone (LH) in the follicular phase of stimulation can have a negative effect on oocyte quality, pregnancy rate and incidence of miscarriage. The aim of the present study was to examine the effects of highly purified follicle stimulating hormone (FSH HP) on ovarian stimulation and particularly on nuclear maturity and morphological appearance of the oocyte in intracytoplasmic sperm injection (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
1
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(15 citation statements)
references
References 19 publications
0
13
1
1
Order By: Relevance
“…In our study, we also saw a trend toward decrease in the days of stimulation with recombinant FSH and in the total dose of recombinant FSH in the group who received recombinant FSH and LH (group B) and recombinant FSH and recombinant hCG (group C), compared with the group who received only recombinant FSH (group A). On the other hand, this trend in activity was not detected by previous studies where FSH and hMG were compared (18,19).…”
Section: Discussioncontrasting
confidence: 77%
See 1 more Smart Citation
“…In our study, we also saw a trend toward decrease in the days of stimulation with recombinant FSH and in the total dose of recombinant FSH in the group who received recombinant FSH and LH (group B) and recombinant FSH and recombinant hCG (group C), compared with the group who received only recombinant FSH (group A). On the other hand, this trend in activity was not detected by previous studies where FSH and hMG were compared (18,19).…”
Section: Discussioncontrasting
confidence: 77%
“…Earlier studies found a higher percentage of mature oocytes in patients treated with FSH than in patients treated with hMG (19,27); however, more recent studies could not identify any significant difference (28)(29)(30). Embryo quality also was found to be comparable (30).…”
Section: Discussionmentioning
confidence: 84%
“…There was a strong tendency of predominant use of rFSH in the HSA-supplemented G2 group. This might contribute to the higher yield of MI oocytes in the HSA-supplemented G2 group (17).…”
Section: Discussionmentioning
confidence: 98%
“…The type of ovarian stimulation implemented in the donor cycles has a major effect on embryo quality and clinical outcomes (37)(38)(39)(40). Consequently, oocyte quality varies among individuals as well as among cycles.…”
Section: Figurementioning
confidence: 99%